Screening of Persea borbonia clones for resistance to the laurel wilt pathogen, Raffaelea lauricola. Issue 5 (8th October 2022) - Hughes, Marc A.; Smith, Katherine E.; Sims, Andrew; Zhang, Junli; Held, Benjamin W.; Blanchette, Robert A.; Smith, Jason A.
Abstract: Laurel wilt, caused by the fungus Raffaelea lauricola, has caused widespread mortality to Persea borbonia across the southeastern United States. The invasive ambrosia beetle vector of the pathogen, Xyleborus glabratus, attacks and infects trees, leaving only P. borbonia seedlings, saplings, and stump sprouts in heavily affected areas. To facilitate mitigation of this ecological damage, we initiated a screening program for laurel wilt disease resistance. We established circular field plots (0.08 hectare) in six significantly impacted sites, measured laurel wilt epidemiological characteristics, and selected 61 survivor P. borbonia ortets (≥7.5 cm diameter at breast height [DBH]) for vegetative propagation, screening, and monitoring. Disease incidence in the plots ranged from 50% to 87% of P. borbonia stems thicker than 2.5 cm DBH and ortet survival per site ranged from 0% to 70% a decade after initial selection. Clonal ramets from 38 survivor ortets were out planted and screened for resistance to R. lauricola in a series of field inoculation trials. Results indicate variable levels of host susceptibility and suggest rare individuals exist with tolerance to R. lauricola . Scanning electron microscopy imaging of xylem samples from three infected P. borbonia clones suggests that reduced tylose production and granular deposition in xylem lumina are associated with increased resistance to R. lauricola . Results from this study will aid in the selection of disease‐resistant P. borbonia germplasm for restoration plantings in affected sites and provide new insights into the host–pathogen interaction of this deadly vascular disease.